Sculptural Portraits, Artistic Traditions of Ancient Lahore - Khalid, Kanwal (Ancient Pakistan, 2021)
There is not much of evidence available regarding the ancient city of Lahore. History is shrouded in mystery and the archaeological evidence is almost non-existent. In this scenario of scarcity of evidence, it’s almost a miracle when we come across some visual evidence related to this period, no matter how meagre it is. Current research is based on such specimens, which were acquired through very unconventional methods but they are important enough not to be ignored. These are the small sized sculptural heads of terracotta discovered not during some formal excavation but by digging the earth few meters deeper than usual. The detailed study of these objects not only confirms their antiquity but it also reveals the fine aesthetics and high level of skill involved.